Disciplinary Measures Where Exists an Alleged Violation of a Collective Agreement

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryA majority of the Board (the union representative dissenting) is of opinion that unless the obeying of an order would constitute an infraction of the law or a safety or health hazard to the employee, the order should be obeyed.Quebec Iron and Titanium Corporation and l'Union des Ouvriers du Fer et du Titanium de Sorel. Jules Poisson, J. Président; Raymond Caron, Company representative; Gérard Picard, union représentative, dissenting. Ministère du Travail, Province de Québec, Bulletin d'Information, no. 1553, 15 mai 1961.